2003
DOI: 10.1038/sj.cdd.4401222
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila model to study the functions of TWIST orthologs in apoptosis and proliferation

Abstract: The twist gene has been characterized for its role in myogenesis in several species. In addition, in mammalian cultured cells, it has been shown that twist is a potential oncogene antagonizing p53-dependent apoptosis. To study, in vivo, the role of twist in apoptosis and proliferation, we constructed transgenic Drosophila lines allowing ectopic expression of different twist orthologs. We report that: (i) Drosophila twist induces apoptosis and activates the reaper promoter, (ii) nematode twist induces arrest of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
4
16
0
Order By: Relevance
“…31 A subsequent study using the Drosophila model to study the functions of Twist orthologs in apoptosis shows that Twist inhibits the p53 pathway independent of ARF and MDM2. 35 Recently, Shiota et al find that Twist directly interacts with the DNA binding domain of p53 to suppress its DNA-binding and transcriptional activity to repress downstream target gene expression. 36 Interestingly, we find that Twist reduces p53 mRNA expression and promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…31 A subsequent study using the Drosophila model to study the functions of Twist orthologs in apoptosis shows that Twist inhibits the p53 pathway independent of ARF and MDM2. 35 Recently, Shiota et al find that Twist directly interacts with the DNA binding domain of p53 to suppress its DNA-binding and transcriptional activity to repress downstream target gene expression. 36 Interestingly, we find that Twist reduces p53 mRNA expression and promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…38 In humans, a germline mutation and reduced expression of TWIST are responsible for Saethre-Chotzen syndrome. 39 TWIST has been invoked to play a role in the development and progression of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the strong expressions of both apoptosis regulators rpr and DIAP1, specifically at the D/V boundary of the wing disc, are in favor of a precise regulation of cell survival in this area. 40,41 In addition, the fact that vg is highly expressed in the same area and is absolutely required for wing pouch development, led us to monitor cell death regulators expression in both wild-type and vg null / þ discs. 7 Using aminopterin, we showed that VG and DHFR are required for the integrity of wing margin cells, in addition to cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…39 But more concerning is the fact that rpr is also expressed in the wing pouch, particularly at the D/V boundary. 40,41 This boundary, therefore, seems to be a quite sensitive area under tight regulation of cell death and cell survival signals. To monitor rpr expression in the different vg, dE2F and DHFR heterozygous contexts, we used a rpr-LacZ reporter transgenic line.…”
Section: Diminution Of Dhfr Activity Leads To D/v Boundary Defectsmentioning
confidence: 99%